How are people with orofacial clefts attended in northwest region of São Paulo state, Brazil? - Francisquetti, Marina Cristine Cano [UNESP]; Gil-Da-silva-lopes, Vera Lúcia; Fett-Conte, Agnes Cristina (FapUNIFESP (SciELO), 2023)
Characterization of specific birth defects is essential for conducting scientific investigations, care and therapeutic strategies. This article describes demographic, clinical and genetic aspects, risk factors and access to treatment of Brazilian patients with orofacial clefts registered in a specialized collaborative center of the Brazilian Database on Craniofacial Anomalies (BDCA). We interviewed 70 individuals with typical orofacial clefts using a standard instrument from the database and subjected them to genetic testing. The patients were grouped as syndromic and non-syndromic. The majority of individuals were of lower middle class, native ancestry and syndromic. There was a significant difference in the type of clefts regarding gender. There was no significant difference between bilateral and unilateral, between the side affected, right and left, or familial recurrence related to type of oral cleft. The risk factor familial recurrence was significantly higher among non-syndromic cases. Etiological factors were identified or suggested in 62.5% of the syndromic cases. There was a delay in diagnosis and in access to treatment in most cases. We concluded that gender, native ancestry and low family income represent risk factors. Furthermore, the distribution by cleft types and gender is similar to previous studies. The results can guide scientific investigations and care policies.
Keywords: Cleft lip; cleft palate; health care